Efficacy and Safety of flecainide p.os. in cardioversion of recent-onset atrial fibrillation (Annals of Medical Research, 2021)
Aim: The aim of the study was to identify the level of safety and the efficacy of flecainide per o.s. in patients with recent-onset (